PDGFRB as a potential therapeutic target of ankylosing spondylitis: validation following bioinformatics analysis - Feng, Xinzhe; Zhu, Shanbang; Yan, Zijun; Wang, Chen; Tong, Wenwen; Xu, Weidong (Cellular and Molecular Biology, 2020)
Ankylosing spondylitis (AS) is a chronic, progressive, and inflammatory disease that mainly affects the central axis joint. Although this disease has already been well documented and studied, its pathogenesis is still not well understood. This study aimed to screen and identify key candidate genes involved in the progression of AS. For this purpose, expression profiles of GSE39340 and GSE41038 were downloaded from the Gene Expression Omnibus and displayed in the form of volcano plots and heatmaps. Differentially expressed genes (DEGs) were identified by the Limma package in R and functional enrichment analyses were performed. Moreover, STRING and Cytoscape were utilized to construct protein-protein interaction (PPI) networks and screen significant modules. Immunohistochemistry (IHC) in tissue chips of AS and normal human synovial tissues was performed to confirm the major proteins associated with its development. Western blotting (WB) and alizarin red staining were applied to validate the expression level of platelet-derived growth factor receptor beta (PDGFRB) and function during osteogenesis differentiation of fibroblasts in AS. A total of 256 DEGs were screened, including 191 up-regulated genes and 65 down-regulated genes. The enriched functions of these identified genes mainly included adherens junction, focal adhesion, and cell-substrate adherens junction. The pathways most highly associated with the progression of AS were TGF-Î² signaling pathway, the Hippo signaling pathway, and the AGE-RAGE signaling pathway. In addition, IHC showed that mitogen-activated protein kinase 1 (MAPK1), C-X-C motif chemokine receptor 4 (CXCR4), and PDGFRB were highly expressed in AS. PDGFRB was found upregulated during osteogenesis of fibroblasts and stimulates osteogenesis in AS. These findings may improve our understanding of the molecular mechanisms controlling AS. Pharmacological targeting of PDGFRB may initiate a possible suppression of bone formation in AS.